Polis Polis is committed to promoting the best ideas and upholding the highest academic standards. (2016)
The first issue of Polis was published by the Department of Political Science and International Relations of the European University of Tirana in 2006. Since then Polis has published 152 original articles and sold hundreds of copies across the Albania
n-speaking area in the Western Balkans.The founding team - led by Henri Cili and Blendi Kajsiu - established a new standard for academic publications in Albania by following the example of reputable Anglo-Saxon journals. Polis$1 (Bs Western-based modes
l, focus on academic rigour, and openness to differing methodological and theoretical strands transformed it into an attractive academic outlet for the dissemination of knowledge and advancement of academic debate in Albania.As the articles became
ever-more diverse, both in breadth and scope, in 2007 Polis became the journal of the Faculty of Social Sciences and Education. In 2010 Odeta Barbullushi became Polis$1 (Bsecond Editor-in-Chief and furthered the journal$1 (Bs growth and transformation into ts
he journal of record for Albanian social scientists. In 2015, with the arrival of Belina Budini as Editor-in-Chief, Polis continued to expand towards the field of humanities to complete its establishment as an academic outlet publishing cutting-edge r
esearch in the social sciences and humanities. In 2017 Elvin Gjevori became Polis$1 (Bfourth Editor-in-Chief leading its greatest transformation. Polis merged with two other journals: Educatio and Justicia, publishing articles in the field of educatis
on and law respectively and changed its working language by publishing articles in English only. To further its internationalisation, besides publishing in English and encouraging internationals scholars to submit articles for publication, Polis estab
lished an international advisory board with some of the most renowned scholars of the Western Balkans. Lastly, thanks to a generous grant by the European University of Tirana, since 2017 Polis articles are publicly available online through a free acce
ss platform at www.polis.uet.edu.al. Over the years, Polis has gone from a small journal of a small department of a small university, into an established academic outlet that is now crossing the confines of Albania to join the European academic de
bate and exchange of ideas about the world we live in and the one we would like to live in the future.